Radio resource management scheme in radar and communication spectral coexistence platform - Kim, Sungwook (Computer networks (Amsterdam, Netherlands : 1999), 2023)
In vehicular environments, the cooperation of radar and communications has been recognized as a promising solution to alleviate the shortage of spectrum resources. In this paper, we investigate the joint radar sensing and communication (JSC) system based on the cooperative spectrum sharing strategy. Via the full cooperation between both radar sensing and wireless communication functionalities, we can avoid the under-utilization of spectral resource while improving system efficiency. To implement our JSC control scheme, we focus on coalitional bargaining solutions according to the cooperative game theory. Especially, the coalitional Nash bargaining solution (CNBS) and coalitional Kalai-Smorodinsky bargaining (CKSBS) are employed to get a mutually desirable solution in the radar-communication coexistence platform. The main ides of CNBS is adopted to distribute the spectrum resource among roadside units, and both radar and communication functions in each individual vehicle. The concept of CKSBS is applied to allocate the spectrum resource for vehicles in order to maximize their payoffs. In the proposed scheme, the CNBS and CKSBS work together to share the surplus of a coalition with the fairness and efficiency properties. The main contribution of our proposed approach is the reciprocal combination of the CNBS and CKSBS to obtain the synergy effect. Finally, numerical results are provided to verify the effectiveness of the proposed scheme for the JSC system operations.